PHYSICIANS' KNOWLEDGE OF COST OF DRUGS - Ahmad, Mushtaq (Journal of Postgraduate Medical Institute, 2013)
Objective: To assess physicians' knowledge of cost of commonly used medications. Methodology: A cross-sectional study done in May 2012 on twenty six (26) physicians (11 Consultants working in Medical units of the three tertiary care hospitals of Peshawar and 15 General Practitionersworking in Peshawar city and Cantonment area). They were asked about the cost of 10 commonlyprescribed drugs. Estimates within 25% of the actual costs were considered accurate. Results: Out of 260 responses, 105 (40.4%) responses of the physicians came up with accurate estimates.No significant difference was found between the responses of GPs and the Consultants [64/150 vs. 41/110(p > 0.05)]. Overall, costs of expensive drugs were more accurately estimated than the inexpensive ones[48/104 vs. 57/156 (p < 0.05)]. Physicians consistently overestimated the costs of inexpensive drugs andunderestimated the costs of expensive ones (p < 0.05). Conclusion: Physicians have inadequate knowledge of cost of drugs which may lead to poor medicationcompliance.